The linkages of Asian and the US stock markets - Razali Chong, Royfaizal; Lee, Chin; Mohamed, Azali (IUP Publications, 2009)
The issues of international stock market linkages have already been investigated over the time. Many researchers and economists are concerned about the relationship between the Asian stock markets and others after the Asian Financial Crisis. This paper aims to examine the interrelationship between the Asian stock markets namely, Malaysia, Singapore, the Philippines, Thailand, Indonesia, China, Japan, Korea, and the US stock markets. The data consists of weekly stock indexes. The total samples are separated into three subperiods. First period is pre-crisis period spanning from January 1990 to June 1997. Second period is during-crisis period spanning from July 1997 to June 1998. Third period is post-crisis period spanning from July 1998 to February 2009. The empirical results show that the number of significant cointegrating vector is higher during the crisis periods compared to other periods. Granger-causality based on Vector Error Correction Model (VECM) showed that stock markets of Thailand, Japan and China are exogenous before, during and after the crisis respectively. This paper concludes that the linkages between the Asian and the US stock markets are stronger in the post-crisis period.